Sistem Sop untuk Penanganan Masalah Piutang Cash Basis di PT. Martindo Fine Foods - Herliani; Yuddy Giovanna Priscilla (ConCEPt - Conference on Community Engagement Project, 2024)
A very effective method of retaining existing customers and attracting new customers is through the implementation of credit sales. Credit sales are also a strategy used by Pt. Martindo Fine Foods to increase profits. However, credit sales are also a big risk for Pt. Martindo Fine Foods because customers do not pay off their receivables on time and become an obstacle for the company in collecting receivables. Therefore, the author designs clear SOP policies and work procedures for handling receivables problems with the aim of increasing the effectiveness and efficiency of receivables collection. To determine the success rate of this study, the data collection technique in this study is to distribute questionnaires to related sections, namely Finance, Sales / Marketing, and sales admin sections. The results of the questionnaire that has been filled out by the three positions will be tested manually with the Likert Scale. The results of the questionnaire that had been filled out by 13 respondents showed that the SOPs implemented had run smoothly and received good feedback from the three positions.